2010
DOI: 10.1002/ajhb.21044
|View full text |Cite
|
Sign up to set email alerts
|

Physical and psychological health of first and second generation Turkish immigrants in Germany

Abstract: Recent studies in Germany suggest that first generation Turkish immigrants have lower mortality rates compared to native Germans. Conversely, studies examining morbidity, though not national in scope, have demonstrated that first generation Turks may have poorer health than native Germans. Additionally, little is known about the health of the emerging second generation Turkish population in Germany. To evaluate the discrepancy between mortality and morbidity trends and contribute to a better understanding of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 48 publications
3
27
0
6
Order By: Relevance
“…While it is generally understood that immigrants may benefit from new opportunities in the destination country, a number of studies have shown that migration is one of the most demanding events in life, as it is often associated with loss and can disrupt the life course (Kuo 1976;Bhugra 2004;Carta et al 2005). A number of studies have demonstrated that elderly migrants report having worse mental health than nonmigrants (Rosmond, Nilsson, and Björntorp 2000;Silveira et al 2002;Abbott et al 1999;Fokkema and Naderi 2013;Milewski and Doblhammer 2015) and that migrants' mental health decreases as their duration of stay increases (Wu and Schimmele 2005;Kotwal 2010).…”
Section: Bridging Interethnic Social Capital: the Exogamy Gain Hypothmentioning
confidence: 99%
“…While it is generally understood that immigrants may benefit from new opportunities in the destination country, a number of studies have shown that migration is one of the most demanding events in life, as it is often associated with loss and can disrupt the life course (Kuo 1976;Bhugra 2004;Carta et al 2005). A number of studies have demonstrated that elderly migrants report having worse mental health than nonmigrants (Rosmond, Nilsson, and Björntorp 2000;Silveira et al 2002;Abbott et al 1999;Fokkema and Naderi 2013;Milewski and Doblhammer 2015) and that migrants' mental health decreases as their duration of stay increases (Wu and Schimmele 2005;Kotwal 2010).…”
Section: Bridging Interethnic Social Capital: the Exogamy Gain Hypothmentioning
confidence: 99%
“…However, there is a lack of data about the HNA antigen frequency in the Turkish population. As many as 1.71 million people in Germany have Turkish citizenship, and about 750,000 feature a German passport since 1990 (9). Thus, Germany is the country with the largest Turkish population behind Turkey (10).…”
Section: Introductionmentioning
confidence: 99%
“…Another study looking at Vietnamese immigrant women in the USA however, found no relationship between mental health and LoS (Brown et al, 2010). Further, among skilled workers in New Zealand and Turkish men (but not women) in Germany, mental health status appears to be positively related to LoS (Kotwal, 2010;Pernice et al, 2009). These studies suggest that LoS may not have the same relationship with mental health across all immigrant groups, perhaps due to the complexity of the migration experience, including acculturation.…”
Section: The Role Of Losmentioning
confidence: 92%